DESCRIPTION OF THE RESULTS OF THE CLOTTING TIME EXAMINATION OF LEE AND WHITE METHOD IN DIABETES MELLITUS PATIENTS AT TOTO KABILA HOSPITAL - Yusri Halada; Natan Pasiga; Mentari Afrilia Besi (LP2M Universitas Bina Mandiri Gorontalo, 2021)
In diabetes mellitus sufferers, there is a hypercoagulation state caused by hyperglycemia, hyperinsulinemia and insulin resistance. This can lead to changes in the components that play a role in the function of hemostasis, causing an increase in coagulation activity with a decrease in fibrinolytic activity. The purpose of this study was to determine the results of the blood clotting time using the Lee and White method in patients with Diabetes Mellitus. This research uses descriptive quantitative research methods. The total sample used was 20 patients with accidental sampling technique. Using univariate data analysis techniques processed through the IBM SPSS Statistic V25.0 program. The results of the study showed that 60.0% of patients with normal blood clotting time and 40.0% with prolonged clotting time. It is recommended for people with Diabetes Mellitus in addition to controlling blood glucose levels, it is also expected to check blood clotting time.